Molecular metabolites – biomarkers of oxidative stress in healthy human breath during normobaric hyperoxygenation. (October 2022) - Moukhamedieva, L.; Dolch, M.; Ozerov, D.; Fetter, V.; Lenic, J.; Kornienko, A.; Grosser, J.; Tsarkov, D.; Roth, P.; Nitzer, R.
Abstract: Volatile organic compounds (VOCs) – biomarkers of oxidative stress in breath of 25 healthy volunteers were analyzed using gas chromatography – mass spectrometry in two series of experiments: 1- and 2-h of normobaric exposure to 100% medical oxygen while resting comfortably in seated position. Randomization of the breath study made it possible to determine VOCs responding to the oxygen exposure: ethane, isoprene, propane, 3-methylhexane, heptanone-2, 2-methylhexane, butane, isobutane, methylcyclopentane, 3-methylbutanal, 2-methylpentane. The biomarkers, which are typical for oxidative stress, were verified using discriminant analysis that allowed us to exclude ethane, isoprene, propane, 2-methylhexane, butane, isobutene and methylcyclopentane from the mathematical model due to the low information content for the forecasting model. Discrimination analysis was conducted in a stepwise mode, which is based on minimization of the Wilkes coefficient (λ) using standard algorithms of the Statistica Statsoft (version 8). Data discrimination allowed to develop a mathematical model and to establish four biomarkers of oxidative stress: 3-methylbutanal, heptanone-2, 3-methylhexane, 2-methylpentane. The predictive model was cross-validated. The forecast accuracy of the developed model is 70%. Highlights: Exhaled air of a human has chemical biomarkers that respond to oxygen inhalation. Most rapidly developing methods of metabolic diagnostics. Non-invasive express studies of human's functional state in real time. Physiological adaptation to spaceflight conditions.